Adult hamartoma of the chest wall: A case report - Bai, Dong; Liu, Yan-han (Frontiers in Oncology, 2022)
Abstract: This paper retrospectively analyzed the case data of an adult hamartoma of the left chest wall, and combined with the literature analysis, to discuss the clinical characteristics, imaging diagnosis and differential diagnosis of hamartoma. CT and MRI findings of the patient showed medial occupation of the left serratius anterior muscle, with visible fat and calcification. Different from the previous reports of chest wall hamartoma in terms of age, location and imaging characteristics, this case had certain characteristics, and the diagnosis needed pathological confirmation after surgical resection.